Tailoring the substrate of thin film reverse osmosis membrane through a novel Î²-FeOOH nanorods templating strategy: An insight into the effects on interfacial polymerization of polyamide - Suzaimi, N.D. (Elsevier B.V., 2022)
The tailoring of the physico-chemical properties of thin film composite (TFC) membranes is essential to augment their separation performances. Maintaining a good balance between water productivity and rejection is one of the important criteria for efficient water treatment. This work reports a nanomaterial-enabled templating strategy used for the construction of a TFC substrate layer. Beta ferric oxy-hydroxides (Î²-FeOOH) nanorods were used as a pore forming template for polysulfone (PSf) substrate. The templating strategy using Î²-FeOOH nanorods increased the porosity and pore space connectivity of the PSf substrate, hence facilitating the formation of homogenous and defect-free polyamide selective layers through interfacial polymerization (IP) on top of the PSf substrate. The best membrane, a-TFC Î²2 which was fabricated using etched PSf substrate preloaded with 1 wt Î²-FeOOH exhibited an increase in water permeance by 3-fold compared to the neat TFC membrane while maintaining NaCl rejection of 97.5. Furthermore, the templating strategy endowed the membrane with better 72 h operational stability, where the water permeance and selectivity were not much deteriorated compared to that of neat membrane. This study demonstrates the feasibility of using substrate templating technique to finetune the porosity and surface pore properties for an optimized IP reaction and hence, enhancing the desalination performance. Â© 2022 Elsevier B.V.